INFLUENCE ENHANCEMENT COMPETENCE USE TECHNOLOGY AND DEVELOPMENT CAREER TO EMPLOYEE PERFORMANCE IMPROVEMENT AT THE PALEMBANG CITY TVRI OFFICE - Bela Sapira; Sabeli Aliya (Jurnal Ekonomi, 2023)
The importance of increasing competence in the use of technology and career development in the context of improving employee performance has become a major concern in the world of work which continues to develop. This study aims to analyze the impact of increasing competence in the use of technology and career development on improving employee performance at the TVRI Palembang City Office. The research method used is a quantitative approach by collecting data through a survey using a Likert questionnaire. The collected data were analyzed through multiple linear regression techniques to examine the relationship between the competency variables for technology use and career development and employee performance. The findings show that career development has a significant positive effect on employee performance, while increasing competence in the use of technology does not have a significant effect on performance. However, the results of the simultaneous analysis show that the two factors together have a significant positive influence on improving employee performance at the TVRI Palembang City Office. In conclusion, improving employee performance in the media environment requires attention to career development and competence in the use of technology in a comprehensive manner.